Hog's Exit : Jerry Daniels, the Hmong, and the CIA - Morrison, Gayle (Book collections on Project MUSE., 2013)
"This book examines the unique personality and reported death of a man who was a pivotal agent in U.S./Hmong history. Friends and family share their memories of Daniels growing up in Montana, cheating death in Laos, and carousing in the bars and brothels of Thailand. First-person accounts from Americans and Hmong, ranchers and refugees, State Department officials and smoke jumpers capture both human and historical stories about the life of this dedicated and irreverent individual and offer speculation on the unsettling circumstances of his death. Equally important, Hog's Exit is the first complete account in English to document the drama and beauty of the Hmong funeral process."--Amazon.com.